“Técnica de Mckenzie como tratamiento de la lumbalgia crónica del adulto. Hospital Básico Militar N°11-BCBG Riobamba, 2018” - Pugachi Castro, Jenifer Catherine (2019)
In this project of investigation there appeared as aim the application of Mckenzie's technology in lumbar pain chronicle for the decrease of the pain, and to improve the mobility of the lumbar column in the patients who come to the area of rehabilitation of the Basic Military Hospital N° 11-BCBG with a population of 25 patients in whom there applied fundamental tools to himself as the clinical history physiotherapy visual analogical scale of pain (EVE) and Laségue's test for the initial and final valuation of every patient. The type of investigation is longitudinal since it was realized in a time determined for the application of the technology. Also it is documentary since on the basis of the analysis of theories and concepts stipulated in books, scientific articles, magazines and information that relates her to Mckenzie's technology and the pathology lumbar pain chronic being of quantitative type, gathering the information on the basis of the numerical valuation and a statistical analysis as age, sex, occupation and pain, obtaining this way proved for the investigation. Finishing with the treatment and expiring with the aims there was realized the comparison of the initial evaluation with the final, being able to demonstrate favorable results by means of the application of Mckenzie's technology for lumbar pain chronicle verifying so it is effective for the relief of the pain in the lumbar zone.